2007
DOI: 10.1507/endocrj.k06-194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Pre-Operative Rapid BRAF Analysis for Papillary Thyroid Cancer

Abstract: Abstract. The activating point mutation of the BRAF gene, BRAF T1799A , is the most common and specific genetic alteration in adult papillary thyroid carcinoma (PTC) and a possible marker of malignant potential of PTC. We have applied the PCR-RFLP method using fine-needle aspiration biopsy samples not only to our clinical practice but also to the international medical assistance effort around the Semipalatinsk Nuclear Testing Site in Kazakhstan. Seventy-seven cases (100 nodules) from Japan and 131 cases (137 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…Recently, a new molecular marker has been found to increase the accuracy of FNAB cytological examination. Indeed, BRAF mutation analysis of FNAB has been reported to have high diagnostic specificity to detect PTC in previous studies examining 1153 FNAB samples with different techniques, such as RFLP, direct sequencing, pyrosequencing, real-time allele-specific amplification, and mutant allele-specific PCR amplification (3)(4)(5)(6)(7)(8)(9)(10)(11). In the present study, 469 FNAB samples, obtained from suspicious thyroid nodules, were analyzed for BRAF V600E mutation by direct sequencing and RFLP.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recently, a new molecular marker has been found to increase the accuracy of FNAB cytological examination. Indeed, BRAF mutation analysis of FNAB has been reported to have high diagnostic specificity to detect PTC in previous studies examining 1153 FNAB samples with different techniques, such as RFLP, direct sequencing, pyrosequencing, real-time allele-specific amplification, and mutant allele-specific PCR amplification (3)(4)(5)(6)(7)(8)(9)(10)(11). In the present study, 469 FNAB samples, obtained from suspicious thyroid nodules, were analyzed for BRAF V600E mutation by direct sequencing and RFLP.…”
Section: Discussionmentioning
confidence: 90%
“…Point mutations in the BRAF gene, implicated in the neoplastic transformation of follicular cells, represent a specific molecular marker for papillary thyroid carcinoma (PTC) and PTC-derived cancers, characterizing up to 45% of PTCs. Previous studies have evaluated the presence of BRAF V600E mutation in FNAB from suspected thyroid nodules, with a prevalence of 62% mutated BRAF PTCs and variable sensitivity and specificity due to differences in the population studied and to the experimental methods employed (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The aim of the present study is to evaluate whether BRAF V600E mutation analysis could increase the diagnostic accuracy of FNAB for PTC in suspicious thyroid nodules of patients referred to a single institution.…”
Section: Introductionmentioning
confidence: 98%
“…The results of BRAF testing in 2766 FNA samples have been reported in 18 prospective and retrospective studies. 65,66,69,70,[79][80][81][82][83][84][85][86][87][88][89][90][91][92] Among 581 BRAF-positive nodules tested in FNA samples in these studies, 580 were papillary carcinomas on pathological examination of the resected nodules, whereas one was diagnosed as a benign nodule, 92 resulting in the false-positive rate of 0.2%. This reportedly benign nodule had a histopathological diagnosis of 'atypical nodular hyperplasia' and was not examined using modern immunohistochemical techniques that are helpful in the diagnosis of thyroid malignancy in difficult cases.…”
Section: Molecular Analysis Of Fna Samplesmentioning
confidence: 99%
“…1B [12]). The high prevalence of BRAFV600E (89.5%) was more than expected, however, it should be noted that recent study by Kumagai et al have also reported similar prevalence of BRAF somatic mutation in Japanese patients [13]. Alternatively, the high prevalence may reflect relative enrichment of advanced PTCs in the specimens analyzed in the present study, although there are some controversies in the correlation between BRAF mutation and aggressiveness of PTC [14,15].…”
Section: Resultsmentioning
confidence: 38%